Talous, sääntely, ohjaus Tarkastuksen ja valvonnan ajankohtaiskysymyksiä - Kihn, Lili-Anne; Oulasvirta, Lasse; Ruohonen, Janne; Rönkkö, Jaakko; Wacker, Jani (Tampere University Press, 2019)
This edited book ("Finance, Regulation, Steering - Current Topics of Audit and Control") provides original research about various current auditing and evaluation topics. Over the past decade, the field of auditing has experienced substantial changes. The articles cover, for instance, such topics as audit quality and price of auditing, performance of internal auditing, XBRL and the debt costs, risk management in local governments and ownership steering of government-owned-enterprises. This book will be of value to practitioners, students and academics interested in contemporary aspects of external and internal auditing, evaluation and oversight of service providers and evaluation.